A new species of narrow-mouthed frog of the genus Chiasmocleis Méhelÿ 1904 (Anura, Microhylidae) from the Amazonian rainforest of Brazil - Peloso, Pedro Luiz Vieira; Sturaro, Marcelo José (Zootaxa, 2008)
A new species of microhylid frog of the genus Chiasmocleis from the Amazonian rainforest of northern Brazil, in the states of Amazonas, Mato Grosso, Pará and Rondônia, is described and illustrated. The new species is characterized by the combination of: large size for the genus; robust body; finger I well developed; toe I developed; toes of males extensively webbed, of females basally webbed; toes fringed; dermal spines on the anterior portion of chin in males. An osteological description and brief notes on natural history are also given. Tadpole and advertisement call are unknown. The species was found in several herpetological collections misidentified as Chiasmocleis bassleri, C. shudikarensis or C. ventrimaculata, and a comparison with those species and comments on the taxonomy of the genus are provided.